Kewirausahaan merupakan kunci utama untuk meningkatkan perekonomian negara - Bunga Indah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Entrepreneurship has become the main focus of economic development in various countries. The role of entrepreneurship in improving economic prosperity has been widely recognized, especially in creating jobs, increasing per capita income, and encouraging innovation and economic growth. This research aims to investigate in depth how entrepreneurship can be the main driver for achieving sustainable economic prosperity. The research method used is a literature review, exploring various concepts and theories related to the role of entrepreneurship in the context of economic prosperity. The analysis results show that entrepreneurship not only contributes to job creation, but also facilitates the growth of small and medium enterprises, expands access to economic resources, and increases competitiveness and innovation. Therefore, policies that support entrepreneurship and create a conducive environment for the development of small and medium enterprises are essential to improve overall economic prosperity. The implications of this research provide a better understanding of the importance of entrepreneurship in creating an inclusive and sustainable economy, as well as providing a basis for formulating more effective policies in advancing the entrepreneurial sector.